ANALISIS HUKUM ISLAM DAN HUKUM POSITIF TERHADAP FAKTOR-FAKTOR PENYEBAB PENCERAIAN DI KALANGAN PASANGAN MUDA: STUDI KASUS DI KABUPATEN KLATEN - Naufal Ahmad Fauzan; Muhammad Yassir (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The issue of increasing divorce rates among young couples in Klaten Regency indicates vulnerability in family resilience, particularly among couples married for less than five years. This study aims to analyze the factors causing divorce among young couples and examine them from the perspective of Islamic law and Indonesian positive law. The method used is qualitative research with a case study approach, through in-depth interviews with judges at the Klaten Religious Court and analysis of court decisions, laws and regulations, and literature on fikih munakahat. The results of the study show that internal factors include economic problems, constant disputes and arguments, and mental and emotional immaturity. External factors include infidelity influenced by social media, family interference, and dependence on parents. From an Islamic law perspective, these factors can be considered valid reasons for divorce after reconciliation efforts have failed, with divorce being considered a last resort. Meanwhile, positive law through Law No. 1 of 1974 and the Compilation of Islamic Law stipulates that divorce can only be carried out through the courts with sufficient reasons and valid evidence. In conclusion, divorce among young couples in Klaten is influenced by a combination of internal and external factors that are normatively recognized in Islamic law and positive law as valid grounds for divorce.